2012
DOI: 10.1194/jlr.p029223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fenofibrate and atorvastatin on VLDL apoE metabolism in men with the metabolic syndrome

Abstract: Hypertriglyceridemia, a key feature of the metabolic syndrome (MetS), is associated with increased risk of cardiovascular disease (CVD) ( 1 ). It is the most consistent lipid disorder in subjects with obesity and type 2 diabetes. Hypertriglyceridemia is primarily related to dysregulated triglyceride-rich lipoprotein (TRL) metabolism, including overproduction of very low-density lipoprotein (VLDL) particles and delayed catabolism of TRL and their remnants ( 2 ). These abnormalities are a collective consequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…In various clinical intervention studies, fenofibrate treatment has shown a consistent increase in apoAII, whereas the effect on apoAI is less consistent (3036, 59). In this study, fenofibrate treatment increased apoAII significantly, whereas no significant effect on apoAI was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In various clinical intervention studies, fenofibrate treatment has shown a consistent increase in apoAII, whereas the effect on apoAI is less consistent (3036, 59). In this study, fenofibrate treatment increased apoAII significantly, whereas no significant effect on apoAI was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription grade formulations of omega-3 fatty acids given in doses of 2–4 g usually decrease serum triglycerides (TG) about 30% (24), whereas 160 or 200 mg fenofibrate decrease serum TG about 30–50%. Many studies have investigated the effects of omega-3 fatty acids and fenofibrate on circulating levels of apolipoproteins (2543). Although apoAI, apoAII and apoB have been extensively studied, the effects of omega-3 fatty acids or fenofibrate on total circulating levels of apoCIV, apoJ (clusterin), apoAIV, apoL1, apoD or apoF have not been investigated in clinical studies to the best of our knowledge.…”
mentioning
confidence: 99%
“…Very-low-density lipoproteins (VLDL) transport triglycerides (TG) from liver to peripheral tissues providing an energy source. Plasma levels of VLDL are defined by the rate of clearance from plasma and the rate of hepatic secretion, so an imbalance between these two processes will lead to dyslipidemia, highly associated with increased risk of cardiovascular disease [1, 2], which is one of the extrahepatic complications of nonalcoholic fatty-liver disease (NAFLD) [3]. Individuals with NAFLD exhibit disrupted VLDL metabolism [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that lipid-lowering therapy with atorvastatin and fenofibrate leads to reduction of apoE concentration in VLDL [43, 44]. Similarly, the interaction between liposomes and VLDL caused a decrease in the apoE concentration in VLDL (Fig.…”
Section: Discussionmentioning
confidence: 98%